Does consumer‐firm affiliation matter? The impact of social distance on consumers' moral judgments. Issue 12 (25th September 2019) - Lo, Carolyn J.; Tsarenko, Yelena; Tojib, Dewi
Abstract: When the leader of a firm commits a professional transgression, how would customers' judgments of the transgressor's professional performance and immorality differ from those of noncustomers'? This research answers this question by investigating factors that explain the discrepancy in moral judgments between noncustomers and customers affiliated with the firm of a transgressing leader. Drawing on construal level theory, our two experimental studies consistently demonstrate that relative to high social distance (i.e., noncustomers), low social distance (i.e., customers) leads to more positive judgments of the transgressor's professional performance, but differences in the social distance do not directly lead to disparities in judgments of immorality. Social distance, however, affects both performance and immorality judgments when mediating mechanisms (conscious and nonconscious moral reasoning) are accounted for, such that low social distance indirectly influences customers to be more lenient in not only their performance judgments but also their immorality judgments. This research contributes to the topic of morality that permeates the current discourse on ethical business transgressions and, in particular, to an understanding of specific mechanisms that guide consumers' moral judgments.